Hubungan Lamanya Penggunaan Kontrasepsi Suntik Depo Medroxyprogesterone Acetate dengan Kadar Glukosa Darah Puasa di PMB Yulida Ti’ani - Dika Tri Muzayana; Ari Kusmiwiyati; Annisa Annisa (Poltekkes Kemenkes Malang, 2020)
The use of contraception is inseparable from various side effects, especially in long term use. One of the side effects of long term use of DMPA is a disorder of blood glucose tolerance. This study aims to analyzed the relationship between the duration of use DMPA injection contraception and fasting blood glucose levels. This is a quantitative research with cross sectional design. The population of this study was 48 respondents of DMPA injection contraception in PMB Yulida Tiani. Sample of 30 respondents was taken by using purposive sampling technique with regarding the inclusion and exclusion criteria. Data collection use interview guidelines and fasting blood glucose laboratory tests. The results of this study using Spearman Ranked with p equal 0.1 and p table 0.306 obtained from the value of p value is greater than p table, 0.522 is greater than 0.306. Which means that H0 was received, so, there was no significant relationship between the duration of Depo Medroxyprogesterone Acetate injection contraceptive use and fasting blood glucose levels. The result of this study showed that 54,8 percent was used DMPA injection contraception for 24 until 65 months and 77,4 percent have normal blood glucose levels between 60 until 100 gr for dL or within normal limits. Therefore, DMPA injection contraception was safed to use for long time as long as the acceptor have not any risk of Diabetes Mellitus.